(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
With the development of the competitive context and the need to move forward in the face of emerging challenges, it has become imperative for institutions and organizations to move towards adopting organizational learning tools, which is what the study investigated in terms of studying the role of contemporary organizational structures (team structure, virtual structure, and network structure) in the adoption and enhancement of Organizational learning as a working approach for workers in the Ministry of Finance - the central administration which enables departments and administrative units to invest and use knowledge. As the descriptive approach was relied on to investigate the research problem, and a simple random sample was taken from workers in the central administration in the Ministry of Finance and a questionnaire was distributed to (200) Employee (148) questionnaires were retrieved, and through the statistical program (SPSS V.26), the data was analyzed and the results reviewed; the study has resulted the following: There is an impact of the team structure and the virtual structure of the Ministry of Finance in adopting and enhancing organizational learning; but there was no effect of the network structure on organizational learning, and this was due to the lack of infrastructure related to networking and information communication.